Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s10964-013-0085-4
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement in the High School Years: The Changing Role of School Engagement

Abstract: School engagement is an important theoretical and practical cornerstone to the promotion of academic accomplishments. This article used a tripartite-behavioral, emotional, and cognitive-model of school engagement to assess the relationship between school engagement and academic success among high school students, and to determine whether a reciprocal relationship exists between these constructs. Data were derived from 710 youth (69% female) who took part in Waves 6 through 8 (Grades 10 through 12) of the 4-H s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 40 publications
4
81
1
8
Order By: Relevance
“…Therefore, future studies should use a more overt indicator of individual, familial, and societal-environmental risk factors. For example, individual risk factors can be measured in terms of academic achievement and school engagement (Chase, Hilliard, John Geldhof, Warren, & Lerner, 2014) as well as psychopathology, sensation seeking, and risk behavior (Zuckerman & Kuhlman, 2000). Familial risk factors can be measured in terms of parental illness (Lopez-Duran, Kuhlman, George, & Kovacs, 2013), divorce (Tein, Sandler, Braver, & Wolchik, 2013), and family adaptability and cohesion (Hamama & Arazi, 2012).…”
Section: Limitations and Future Suggestionsmentioning
confidence: 99%
“…Therefore, future studies should use a more overt indicator of individual, familial, and societal-environmental risk factors. For example, individual risk factors can be measured in terms of academic achievement and school engagement (Chase, Hilliard, John Geldhof, Warren, & Lerner, 2014) as well as psychopathology, sensation seeking, and risk behavior (Zuckerman & Kuhlman, 2000). Familial risk factors can be measured in terms of parental illness (Lopez-Duran, Kuhlman, George, & Kovacs, 2013), divorce (Tein, Sandler, Braver, & Wolchik, 2013), and family adaptability and cohesion (Hamama & Arazi, 2012).…”
Section: Limitations and Future Suggestionsmentioning
confidence: 99%
“…School engagement describes a student’s behavioral, emotional, and cognitive commitment to schooling (Chase, Hilliard, Geldhof, Warrant, & Lerner; Fredricks & McColskey, 2014). It was assessed in terms of three subscales: School Preparation (behavioral engagement), Beliefs about School (cognitive engagement), and Enjoyment of Schoolwork (emotional engagement).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, higher school involvement exposes adolescents to more learning opportunities beyond the classroom, which in turn lead to increased academic skills. Indeed, research has consistently found that higher behavioural involvement (e.g., completing homework, attendance) and emotional involvement (e.g., feeling attached to school, close to teachers) were predictive of better grades (Chase, Hilliard, Geldhof, Warren, & Lerner, 2014;Finn & Rock, 1997).…”
Section: School Involvement and Academic Performancementioning
confidence: 99%